Estimates of Upper Bound for a Function Associated with Riemann-Liouville Fractional Integral via h-Convex Functions. (2nd May 2019) - Wu, Shan-He; Awan, Muhammad Uzair
Abstract : A new identity involving Riemann-Liouville fractional integral is proposed. The result is then used to obtain some estimates of upper bound for a function associated with Riemann-Liouville fractional integral viah -convex functions. An application for establishing the inequalities related to special means is also considered.